New insights into the mixed anionic/cationic collector adsorption on ilmenite and titanaugite: An in situ ATR-FTIR/2D-COS study. (1st August 2021) - Luo, Liping; Xu, Longhua; Meng, Jinping; Lu, Jiahui; Wu, Houqin
Highlights: SHA and DDA are used as mixed collector to separate ilmenite from titanaugite. AFM proved a high selectivity for SHA/DDA adsorbs onto ilmenite and titanaugite. Two-dimensional correlation ATR/FTIR spectroscopy reveal the adsorption mechanism of the mixed collector. Recommended adsorption models for the adsorption of the complex on the surfaces of ilmenite and titanaugite were proposed. Abstract: Elucidation of the co-adsorption characteristics of multiple functional groups will help to screen suitable reagents to improve the floatability and comprehensive utilization of valuable minerals. Herein, salicylhydroxamic acid (SHA), an anionic collector with two functional groups, mixed with a cationic collector dodecylamine (DDA) in ilmenite-titanaugite flotation system was in-depth studied mainly using in-situ attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) combined with the two-dimensional correlation spectroscopic analysis (2D–COS) and X-ray photoelectron spectroscopy (XPS). The highest flotation separation performance, at pH 8–9, can be achieved using the SHA/DDA complex with a molar ratio of 6:1. Moreover, atomic force microscope (AFM) analysis ulteriorly proved the selectivity of the mixed SHA/DDA collector in the ilmenite-titanaugite flotation system. In-situ ATR-FTIR combined with 2D-COS gave the characteristic sequential adsorption and interaction with the functional groups related to SHA/DDA, which was further confirmed in the results of XPS. The preferred adsorption configuration for the adsorption of the mixed collector were drew to explain the flotation separation between ilmenite and titanaugite. It is predictable that the detailed study into the hybrid collectors with multiple functional groups will provide new insights into the design, synthesis and development of more-powerful collectors.